2022
DOI: 10.26508/lsa.202201383
|View full text |Cite
|
Sign up to set email alerts
|

Structure and conformational dynamics of Clostridioides difficile toxin A

Abstract: Clostridioides difficile toxin A and B (TcdA and TcdB) are two major virulence factors responsible for diseases associated with C. difficile infection (CDI). Here, we report the 3.18-Å resolution crystal structure of a TcdA fragment (residues L843–T2481), which advances our understanding of the complete structure of TcdA holotoxin. Our structural analysis, together with complementary single molecule FRET and limited proteolysis studies, reveal that TcdA adopts a dynamic structure and its CROPs domain can sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 52 publications
(111 reference statements)
0
21
0
Order By: Relevance
“…It is widely accepted that the pore-forming region of TcdA/TcdB, which carries a large number of hydrophobic residues, is protected by the DRBD at neutral pH, but partially unfolds and detaches from the DRBD when induced by acidic endosomal pH in order to form a pore ( 5 , 10 , 48 ). Drastic conformational changes could be observed in the pore-forming regions when comparing the structure of TcdA obtained at the neutral pH and a structure of TcdB that was obtained under acidic pH and represents a pore-forming intermediate state ( Figure 4E ) ( 8 10 ). Nevertheless, it has been shown that 5D is able to grip and stabilize a β hairpin motif in TcdB’s pore-forming region, which may subsequently block the acidic pH-induced unfolding of TcdB ( 10 ).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…It is widely accepted that the pore-forming region of TcdA/TcdB, which carries a large number of hydrophobic residues, is protected by the DRBD at neutral pH, but partially unfolds and detaches from the DRBD when induced by acidic endosomal pH in order to form a pore ( 5 , 10 , 48 ). Drastic conformational changes could be observed in the pore-forming regions when comparing the structure of TcdA obtained at the neutral pH and a structure of TcdB that was obtained under acidic pH and represents a pore-forming intermediate state ( Figure 4E ) ( 8 10 ). Nevertheless, it has been shown that 5D is able to grip and stabilize a β hairpin motif in TcdB’s pore-forming region, which may subsequently block the acidic pH-induced unfolding of TcdB ( 10 ).…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, antibodies blocking this step should provide potent protection. We found that AH3 and AA6 can bind simultaneously on TcdA holotoxin ( 8 , 9 ) ( Figure 5 ). Therefore, combining AH3 and AA6 in a hybrid molecule should lead to even higher neutralizing potency because of synergistic binding of both VHHs.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations